1975
DOI: 10.1111/j.1748-1716.1975.tb10038.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characteristics of Fibre Types in Human Skeletal Muscle

Abstract: Muscle biopsy samples were obtained from healthy subjects in order to evaluate quantitative differences in single fibres of substrate (glycogen and triglyceride) and ion concentrations (Na+ and K+) as well as enzyme activity levels (succinate-dehydrogenase, SDH; phosphofructokinase, PFK; 3-hydroxyacyl-CoA-dehydrogenase, HAD; myosin ATPase) between human skeletal muscle fibre types. After freeze drying of the muscle specimen fragments of single fibres were dissected out and stained for myofibrillar-ATPase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
271
2
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 542 publications
(296 citation statements)
references
References 22 publications
21
271
2
2
Order By: Relevance
“…28 In human muscle, the oxidative enzyme activity of type I fibres was higher than type II fibres. 7 On the other hand, we and the other studies 29,30 showed that at least type IIA fibres had a higher SDH activity, which is a tricarboxylic acid cycle enzyme and an index of mitochondrial content, than type I fibres in rat muscles. It Muscle characteristics and body fat accumulation M Suwa et al was therefore reasonable to assume that the relationship between the muscle fibre composition and whole muscle oxidative capacity in humans did not correspond to that in rats.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…28 In human muscle, the oxidative enzyme activity of type I fibres was higher than type II fibres. 7 On the other hand, we and the other studies 29,30 showed that at least type IIA fibres had a higher SDH activity, which is a tricarboxylic acid cycle enzyme and an index of mitochondrial content, than type I fibres in rat muscles. It Muscle characteristics and body fat accumulation M Suwa et al was therefore reasonable to assume that the relationship between the muscle fibre composition and whole muscle oxidative capacity in humans did not correspond to that in rats.…”
Section: Discussionmentioning
confidence: 88%
“…6 The rank order of oxidative capacity in human muscle fibres is I > IIA > IIX. 7 In humans, the percentage of type I fibres has been shown to negatively correlate with percentage body fat. 1,4 The metabolic profiles of skeletal muscle fibre types might be one of the causes of the relationship between muscle fibre composition and body fat accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…25 The metabolic characteristics of type IIa fibers are intermediate between type I and type IIb fibers. 13 Studies investigating the association between fiber type distribution and BP or occurrence of hypertension have, however, found the proportions of the main fiber types to be important, whereas the subclassification of type II fibers into IIa and IIb provides no additional information. 10,22,29,30 A limitation of the present study is that the subjects were not a randomly selected population sample.…”
Section: Discussionmentioning
confidence: 99%
“…12 Type I fibers have a higher oxidative capacity than type II fibers. 13 Muscle fiber-type proportions differ between elite athletes in various types of sports. Endurance sports athletes have a high type I%, but speed and power sports athletes have a preponderance of type II fibers.…”
mentioning
confidence: 99%
“…Correlations have been shown between HSL content and IMTG storage and the oxidative capacity of the skeletal muscle types. 20 HSL activity is increased two-fold in humans in response to moderate-low-intensity exercise. 21 HSL protein expression is greater in oxidative as compared to glycolytic muscle fibres.…”
Section: Mechanisms Of Imtg Accumulationmentioning
confidence: 98%